Developing an aeronautical English training unit based on the ADDIE model in an EFL context - Park, Moonyoung; Huffman, Sarah (The ESPecialist, 2020)
The precision and effectiveness of the communication between air traffic controllers and pilots is quite literally a matter of life or death. Speakers of aeronautical English, the language of communication in the realm of aviation, are required by the ICAO to meet a minimum standard of language performance across the communication skills of listening and speaking, yet miscommunication and misunderstandings across channels persist, potentially resulting in catastrophic collisions and incidents. This English for Specific Purposes (ESP) paper reports on the creation of an aeronautical English training unit guided by principles of the ADDIE (analysis, design, development, implementation, and evaluation) model of instructional design developed to assist Korean army enlisted soldiers and noncommissioned officers who are serving as air traffic controllers in the improvement of integral aeronautical English skills. Designed materials were assessed with the assistance of four subject-matter experts (SMEs) as a pilot test, and results of the evaluation demonstrate the potential for application of the ADDIE model of instructional design for future ESP instructional units.